Effect of the Degree of Inversion on the Electrical Conductivity of Spinel ZnFe2O4. Issue 4 (25th January 2019) - Granone, Luis I.; Dillert, Ralf; Heitjans, Paul; Bahnemann, Detlef W.
Abstract: Spinel ferrites (MFe2 O4, where M is a metal ion) in general, and zinc ferrite (ZnFe2 O4, ZFO) in particular, have recently received considerable attention due to promising results in the field of photocatalysis and, especially, photoelectrochemistry. ZFO exhibits a variable crystal structure in which the distribution of the cations between octahedral and tetrahedral sites in the cubic close‐packed oxygen lattice, i. e., the degree of inversion, is known to depend closely on the synthetic conditions. Although the effect on the magnetic and optical properties is well known, fundamental research is still missing to fully understand the impact of the cation distribution on the photoelectrochemical activity. In this context, an utmost important physicochemical property is the electrical conductivity. In this work, the dielectric properties of ZFO samples with degrees of inversion ranging from 0.07 to 0.20 were investigated. The conductivity of the ZFO samples was found to increase as the degree of inversion increases. At an onset value of the degree of inversion between 0.13 and 0.16, the bulk conductivity increases by two orders of magnitude. This increase is a direct evidence of the high impact of the cation arrangement in the crystal lattice on the electronic properties of ZFO. Abstract : An unexpected increase of the electrical conductivity by two orders of magnitude: The effect of the degree of inversion on the electrical conductivity of ZnFe2 O4 was evaluated. It was found that as the degree of inversion increases, the bulk conductivity increases as well. The electrical conductivity drastically rises by two orders of magnitude when the degree of inversion exceeds an onset value between 0.13 and 0.16.